2022
DOI: 10.1093/bjsopen/zrac012
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and consequences of postoperative pancreatitis after pancreaticoduodenectomy

Abstract: Background Recent studies have suggested postoperative acute pancreatitis (POAP) as a serious complication after pancreaticoduodenectomy (PD) and have speculated on its possible role in the pathogenesis of postoperative pancreatic fistula (POPF). This study aimed to assess the impact of POAP on post-PD outcomes and fistula risk score (FRS) performance in predicting POAP. Methods All PDs at Helsinki University Hospital between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…68 However, there is a growing body of evidence for factors associated with POAP. 9,69 POAP and POPF seem to share the majority of identified risk factors with pancreatic texture, high BMI, narrow duct, operative complexity, non-malignant histology, and male sex predisposing for POAP. 8,9…”
Section: Prediction Of Postoperative Pancreatitismentioning
confidence: 96%
See 2 more Smart Citations
“…68 However, there is a growing body of evidence for factors associated with POAP. 9,69 POAP and POPF seem to share the majority of identified risk factors with pancreatic texture, high BMI, narrow duct, operative complexity, non-malignant histology, and male sex predisposing for POAP. 8,9…”
Section: Prediction Of Postoperative Pancreatitismentioning
confidence: 96%
“…No prediction models for POAP or PPAP exist to date, but one study demonstrated that POPF prediction models could be used to predict clinically relevant POAP (elevated amylase and C-reactive protein over 180 mg/l on second postoperative day), with ua-FRS performing the best with an AUROC of 0.83. 9…”
Section: Prediction Of Postoperative Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology behind pancreatic fistula formation is still not understood. Persistent leakage from the main pancreatic duct or from side branches, a high amount of acinar cells at the transection plane [ 2 ], postoperative pancreatitis [ 3 ], or dysfunction of the Sphincter of Oddi [ 4 ], are considered the probable underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Bonsdorff et al present a retrospective series of 614 patients who underwent pancreatoduodenectomy between 2013 and 2020 at Helsinki University Hospital. 1 The aim of this study was two-fold, first to reconfirm the impact of clinically relevant POAP (CR-POAP) on early outcomes following PD but also to assess the utility of presently used fistula risk scores in predicting CR-POAP. It is acknowledged that the definition of CR-POAP remains an area of evolution 2 , 3 and for this study the authors elected to use the initial definition proposed by my previous work (serum amylase above upper limit of normal day 0–1 and C-reactive protein (CRP) more than180 mg/dl day 1–2) 2 .…”
mentioning
confidence: 99%